2015
DOI: 10.15344/2456-446x/2015/102
|View full text |Cite
|
Sign up to set email alerts
|

Use of 99mTc-labelled Anti-TNF Monoclonal Antibodies to Assess Patients Affected by Inflammatory Arthropathies

Abstract: Nuclear medicine techniques have been applied for many years to assess the activity in patients with different inflammatory arthropathies. The recent development of specific radiopharmaceuticals suggested the possibility to use nuclear medicine in order to clarify the disease mechanisms and predict response to treatment. In this review, we aimed at presenting data concerning the use of 99m Tc-labelled anti-TNF monoclonal antibodies. Few studies have been conducted in patients affected by Rheumatoid Arthritis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The 99m Tc-adalimumab uptake was not evident in all inflamed joints, most likely because not all inflamed joints are characterized by TNF-α expression, this is important for pre-selection of patients for anti-TNF-α therapy. A mini review compared studies using both 99m Tc-infliximab and 99m Tc-adalimumab and concluded that both antibodies are suitable for therapy decision-making purposes in RA 76. Another interesting observation in that study was that patients that showed high pre-therapy uptake of 99m Tc-adalimumab showed more therapeutic benefit when treated with unlabeled anti-TNF mAb 76,77.…”
Section: Applications Of Molecular Imagingmentioning
confidence: 99%
“…The 99m Tc-adalimumab uptake was not evident in all inflamed joints, most likely because not all inflamed joints are characterized by TNF-α expression, this is important for pre-selection of patients for anti-TNF-α therapy. A mini review compared studies using both 99m Tc-infliximab and 99m Tc-adalimumab and concluded that both antibodies are suitable for therapy decision-making purposes in RA 76. Another interesting observation in that study was that patients that showed high pre-therapy uptake of 99m Tc-adalimumab showed more therapeutic benefit when treated with unlabeled anti-TNF mAb 76,77.…”
Section: Applications Of Molecular Imagingmentioning
confidence: 99%
“…To overcome the drawbacks of the excessively long half-life and to reduce non-specific immune recognition, monoclonal antibody fragments and nanobodies (i.e., single-domain antibodies) have been developed. Antibody-based imaging agents have been investigated for their potential application in the diagnosis of autoimmune diseases [99,100], cancer [101,102], and cardiovascular diseases [103].…”
Section: Conjugates For Active Targetingmentioning
confidence: 99%
“…54 Anti-TNF antibodies such as infliximab, adalimumab, golimumab, certolizumab pegol, and etanercept have been developed to treat inflammatory diseases such as rheumatoid arthritis (RA), spondyloarthropathy, psoriatic arthritis, and IBDs. 5561…”
Section: Other Monoclonal Antibodiesmentioning
confidence: 99%